AMP-activated protein kinase - Cordero, Mario D.; Viollet, Benoît 1968- (Switzerland : Springer, 2016)
AMPK has emerged as an important integrator of signals that control energy balance through the regulation of multiple biochemical pathways in eukaryotes. This book focuses on the implications of AMPK as a master metabolic regulator in diseases, including new methods and animal models. The contributions are written by leading experts in the field and give an extensive overview of the current knowledge of AMPK biology and the role of AMPK in health and disease.
Keywords: PROTEINA QUINASAS; ÁCIDO ADENÍLICO; METABOLISMO -- DESÓRDENES; BIOQUIMICA CLINICA